De-industrialisation - Olivier Debande (EIB Papers, 2006)
This paper observes that de-industrialisation has been mostly relative in Europe, with industrial value added and employment shrinking in relative terms, but industrial value added growing in absolute terms - at least until recently. Qualitatively, this relative de-industrialisation has been the result of a number of supply-side factors, including improving labour productivity; changing comparative advantage of countries; and trade liberalisation. Demand-side factors have played a role, too, as rising income levels and population ageing in developed countries have led to changing consumption patterns. Quantitatively, factors internal to advanced economies, such as productivity growth and changing consumption patterns, explain 70 percent of the downtrend in European industrial employment. External trade, including with low-wage economies, is less important, although its role has shown some signs of strengthening in the past decade. All in all, the causes of de-industrialisation do not reflect market failures, and the process should not be resisted. However, it may have transitory economic and social pain as a consequence, which may well warrant public intervention.
Keywords: 330; Deindustrialisierung; Industrieller Strukturwandel; Arbeitsproduktivität; Komparativer Kostenvorteil; Außenhandelsliberalisierung; Einkommensverteilung; EU-Staaten; Japan; USA; Alternde Bevölkerung